Determinants of EMR Adoption and Use by Healthcare Professionals in Developing Countries: A Systematic Review - Oumaima Hafide; Abdelaziz Zitouni; Youness.Lafraxo (Communications of International Proceedings, 2020)
Background: The Electronic Medical Record (EMR) is the backbone of today's global healthcare systems, enabling the management and computerized sharing of all patient medical information. The sharing of medical data between healthcare professionals enables the improvement of the efficiency and quality of healthcare services provided to patients. Despite the promise of EMR use, health care professionals continue to resist its adoption and successful EMR deployment remains a major challenge. Objectives: The objective of this study was to identify and synthesize the determinants of EMR adoption, through a systematic literature review, by healthcare professionals in developing countries. Methods: A systematic literature review was conducted using the PRISMA-P (Preferred reporting items for systematic reviews and meta-analyses) methodology. Articles published between January 2010 and June 2020 that studied the determinants of EMR adoption and acceptance by health professionals in developing countries were identified using five online databases: ScienceDirect, Springer Link, Scopus, Emerald and Sage journals. The selection process excluded duplicate articles and articles that did not directly address the objectives of this study. In the end, 17 articles were included. The extraction of results was done by two researchers, independently. Results: This study included 17 articles that examined the determinants of adoption and acceptance of EMR use by health professionals in developing countries. From these articles, 27 factors were identified and grouped into 4 classes: (1) technological factors (2) individual characteristics of healthcare professionals, (3) organizational and managerial characteristics and (4) social factors. Conclusion: Identifying the determinants of EMR adoption in developing countries is crucial for health system managers and policy makers. It allows them to grasp the expectations of potential users and to adjust EMR deployment strategies in order to successfully integrate the EMR into medical practices.
Keywords: EMR Adoption; EMR Adoption; Developing Countries.